Synthesis of chromium-D-phenylalanine complex and exploring its effects on reproduction and development in Drosophila melanogaster - Dhadde, Shivsharan B.; Kalshetti, Mallinath S.; Thippeswamy, B. S. (Frontiers in Pharmacology, 2023)
The present study was undertaken to explore the effect of Chromium-D-phenylalanine (Cr(D-phe)3) on the reproduction and development of Drosophila melanogaster. Cr(D-phe)3 was synthesized and characterized by infrared spectral analysis, melting point (DSC) and UV spectral analysis. D. melanogaster raised in corn flour agar medium containing 0, 5, 10, 15 and 20 µg/ml of Cr(D-phe)3. The effect of Cr(D-phe)3 was evaluated by observing the larval period, pupal period, percentage of egg hatching, morphometric analysis of eggs, larvae, pupae and adults, fertility, fecundity, lifespan of the emerged flies and levels of antioxidant enzymes such as catalase, glutathione-S-transferase (GST) and superoxide dismutase (SOD) in the supernatant of crushed flies homogenate suspension. The study results indicate that Cr(D-phe)3 showed beneficial effects on reproduction and development in D. melanogaster. Cr(D-phe)3 significantly improved the larval period, pupal period, percentage of egg hatching, morphometric characters of larva, pupa and adult, fertility, fecundity and lifespan of D. melanogaster. Moreover, Cr(D-phe)3 also significantly elevated the levels of catalase (p<0.01), GST (p<0.05) and SOD (p<0.01) in D. melanogaster and results are statistically significant at the dose of 15 µg/ml. The study results indicate that Cr(D-phe)3 have positive effects on the reproduction and development of D. melanogaster. The literature review revealed that there is a strong relationship between the physiology of metabolism and oxidative stress. Several studies propose that Cr(III) influences insulin sensitivity and thereby metabolism of carbohydrates, proteins, and fats and it has antioxidant and anti-inflammatory properties. Hence, the observed beneficial effects of Cr (D-phe)3 on reproduction and development of D. melanogaster may be attributed to its physiological effect on carbohydrate, protein and lipid metabolism and its antioxidant and anti-inflammatory properties.